ONE Liver: A unique, multidisciplinary virtual tool for prospective review of complex liver tumors. Issue 28 (1st October 2022) - Chollet-Lipscomb, Casey; Wolf, Patrick; Bernhard, Matthew R; Maduell, Kelsey; Davidson, Stacey; Bilbrey, Larry Edward; Schleicher, Stephen Matthew
Abstract : 59 Background: Primary and secondary malignancies involving the liver represent some of the most complex cases we see in oncology. These tumors often require multi-disciplinary decision making to determine the optimal treatment. For example, the treatment plan for hepatocellular carcinoma or colorectal cancer metastatic to the liver can often include one of several liver-directed therapy options for cure and/or palliation. Obtaining multiple opinions in an expedited and patient-centered way can be challenging for community oncologists, especially those serving a rural community. We opted to create a virtual tumor board with geographical reach across Tennessee for timely comprehensive evaluation of these patients at Tennessee Oncology (TO), a community oncology network spanning over 30 clinical sites of care. Methods: In January 2021, we created a multidisciplinary team containing specialists in medical oncology, radiation oncology, hepatology, radiology, interventional radiology, and hepatobiliary surgery. Medical oncologists at any TO clinic in Tennessee or Georgia could make referrals to the program within the Electronic Health Record (EHR). The team reviewed all submitted cases bi-weekly either virtually or at a centralized location. Referring providers were not required to attend the tumor boards to expand geographical reach. Recommendations were communicated back to the referring physician by both email and letters scanned into the EHR. Results: Between January 1, 2021 and May 1, 2022, a total of 154 referrals representing 126 unique patients were placed to the ONE Liver tumor board. Thirty-three physicians referred patients across 21 practice locations across the state. The top 3 diagnoses were: metastatic colorectal cancer (53), hepatocellular carcinoma (33), and primary biliary cancers (32). The most common first line recommendations were for therapy with Y-90 embolization, further imaging workup, continued systemic therapy and/or clinical trial evaluation, and stereotactic body radiation therapy. All patients were evaluated within 2 weeks of referral with most evaluated in less than 1 week. 60% of patients evaluated lived more than 25 miles from a tertiary medical center and 28% lived more than 50 miles out. Conclusions: This initiative successfully facilitated efficient and multi-disciplinary evaluation of patients with complex liver tumors living in rural areas. Tumor boards of this type might scale disease expertise across larger geographical locations than traditional in-person tumor boards.